Right-to-Work Laws, the Southernization of U.S. Labor Relations and the U.S. Trade Union Movement's Decline. (December 2015) - Devinatz, Victor G.
This article provides a framework for explaining why the right-to-work (RTW) movement is thriving in the twenty-first century's second decade while outlining how RTW has negatively impacted the U.S. trade union movement. I argue that the recent growth of the RTW movement is due to the Southernization of U.S. labor relations that has led to not only an assault on private sector unionism but on public employee unionism as well. After presenting recent developments concerning RTW legislation, the roots of the Southernization of U.S. labor relations are discussed followed by sections outlining the historical development of the Southernization of both the U.S. working class and U.S. politics before presenting the effects of the Southernization of U.S. labor relations. The article's penultimate section reports on the major economic effects of RTW legislation, primarily through outlining three RTW hypotheses and the associated empirical evidence. The final section proposes a methodology for potentially dealing with the RTW movement given the Southernization of U.S. labor relations.